Blood Transfusion Practices at The Intensive Observation Unit (Ruang Observasi Intensif/ROI) of Dr. Soetomo General Academic Hospital Surabaya - Almira Saskia Sabila; Maulydia; Betty Agustina Tambunan; Edward Kusuma (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Blood transfusion is the process of transferring blood or its components, such as red blood cells, plasma, and platelets, from donor to recipient. The major reason for blood transfusion is anemia and bleeding, frequently seen in critically ill trauma patients in Intensive Observation Unit (Ruang Observasi Intensif/ROI). One of the most prevalent causes of potentially preventable death in trauma patients is uncontrolled bleeding. In addition to controlling the bleeding by surgical or interventional procedures, blood transfusion is carried out to maintain oxygenation to tissue, preventing organ dysfunction due to hypoxia. Objective: This study aimed to determine the profile of blood transfusion carried out on the patients in the ROI of Dr. Soetomo General Academic Hospital. Methods: This retrospective descriptive study was conducted using medical records involving 258 patients who met the inclusion criteria. Results: The result showed that the majority of patients were female, aged 26-35 years, had blood type O, and Rhesus (Rh)-positive, accounting for 55.04%, 26.36%, 39.53%, and 100%, respectively. The most common indication for transfusion was anemia, with a percentage of 69.10%, particularly severe anemia, accounting for 48.45%. Furthermore, 57.36% of patients were from the surgery department, and 36.05% stayed in ROI for 2-3 days. The most common blood component and unit transfused was packed red blood cells (PRC), with a percentage of 57.50% and 439 units at 47.82%. Most of the transfusions, with a percentage of 37.80%, were carried out within 3-4 hours. Some patients were experiencing pruritus, febrile, urticaria, and chills, accounting for 0.39%, 0.39%, 0.39%, and 0.39%, respectively. Conclusion: Understanding transfusion practices, including blood type distribution, can prevent blood shortage, estimate the need for blood among ROI patients in Dr. Soetomo General Academic Hospital, and further ensure that all transfusions are ABO and Rh compatible.